1994
DOI: 10.1111/j.1525-1470.1994.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytic Nevi in Turner Syndrome

Abstract: One morphologic feature of Turner syndrome is increased numbers of melanocytic nevi; however, little attention has been given to their characterization. The development of a melanoma in one of our patients with Turner syndrome prompted this study. We prospectively examined 10 patients with the disease, confirmed by karyotype. All patients underwent full body skin examination noting the number, size, distribution, and degree of clinical atypia of melanocytic nevi. Representative and unusual lesions were photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…It occurs in approximately 1 in every 5,000 female births [1]and has many characteristic clinical features. These include a marked increase in the number of acquired melanocytic nevi [2, 3, 4]although this was not observed in the case report. The median number in TS has been as high as 115 in one study [2], which compares to a range of 20–40 reported for the general population [5].…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…It occurs in approximately 1 in every 5,000 female births [1]and has many characteristic clinical features. These include a marked increase in the number of acquired melanocytic nevi [2, 3, 4]although this was not observed in the case report. The median number in TS has been as high as 115 in one study [2], which compares to a range of 20–40 reported for the general population [5].…”
Section: Discussionmentioning
confidence: 38%
“…These include a marked increase in the number of acquired melanocytic nevi [2, 3, 4]although this was not observed in the case report. The median number in TS has been as high as 115 in one study [2], which compares to a range of 20–40 reported for the general population [5]. The association between TS and nevi has recently been highlighted in a report suggesting that the administration of human growth hormone, routinely administered to girls with TS to increase adult height, might accelerate the growth of nevi and therefore increase the risk of cutaneous melanoma (CM).…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…This observation is also of interest as it suggests the presence of a factor involved in nevus development on the X chromosome. In one study, the median number of nevi in girls with Turner's syndrome was 115, 53 suggesting that the MM risk in these girls based on nevi number alone would be about tenfold that of the general population (where the median number of nevi is in the range of 20±40). 56 However, there is only one reported case in the literature 57 of cutaneous MM developing in a person with Turner's syndrome, and no cases were observed in a registry of 597 Danish TS females 58 with this condition.…”
Section: Nevi As a Genetic Risk Factormentioning
confidence: 97%
“…Studies conflict with regard to the question whether TS is associated with and increased melanoma risk (167,168,395,396). Other skin conditions that have a greater prevalence include pilomatricomas (2.6%) (397, 398), vitiligo (2.7-6%) (399, 400) and halo nevi (18%) (399).…”
Section: Dermatologymentioning
confidence: 99%